Development of Modified Kato Katz Kit as Laboratory Scale Prototype for Early Detection of Soil-Transmitted Helminths (STHs) Infection - Rifqoh Rifqoh; Yayuk Kustiningsih; Jujuk Anton Cahyono (Medical Laboratory Technology Journal, 2021)
Early detection of Soil-Transmitted Helminths (STHs) infection in laboratory medical facilities is one of the government's efforts in its elimination. Government regulations recommend Kato-Katz's quantitative method forthe diagnosis of STHs infection. Kato-Katz's domestic product is not availableyet. This research aims to create a laboratory-scale modified Kato-Katz kit for early detection of STHsinfection by fecal egg counts (FECs) in estimating the number of eggs per gram of stool (EPG).An experimental study was conducted to create a resin template, spatulas, and 3M-adhesive tape as a modified Kato-Katz Kit. 120 Kato-Katz thick smear preparations were done from 30 samples for modified and standard Kato-Katz with duplication. The amount of stool for each was weighed. All Kato-Katz thick smear microscopic examination was done at least 60 minutes by identifying the STHs eggs and counting them.The result for both methods showed no differences in EPG for Trichuris trichiura eggs p-value=0.012 (p<0.05), meanwhile the differences for Ascaris lumbricoides eggs p-value=0.156, and Hookworm eggs p-value=0.102 (p>0.05). Under microscopic examination, some A.lumbricoides eggs morphology was not visible because the adhesive in modified Kato-Katz blurry it, and the Hookworm fragile eggshells made it disappear within less than 60 minutes.The study concluded no difference in EPG for T.trichiura eggs by FECs betweenmodified Kato-Katzas this study product with the standard. It is recommended to improve modified Kato-Katz in further study, especially the adhesive tape, before using it as a quantitative toolforearly detection of STHs infection.